Diseminasi Teknik Pembuatan Minuman Tradisional Pokak Siap Seduh kepada Masyarakat Desa Bringsang Pulau Giligenting - Mojiono, Mojiono (Universitas Jenderal Soedirman, 2024)
Giligenting is a small island near Madura. With its exotic beach , the island may generate positive economic impacts to local community. To strengthen this idea, we performed community service – KKNT, which triggered the production of local products designed for tourism in Bringsang, Giligenting island. In this regard, KKNT mission was to develop traditional beverage ”pokak”. The product comprised of various spices and natural ingredients, primarily ginger, lemongrass, and (palm and cane) sugar. The community service aimed to educate local people on how to produce ”pokak”, divided into three stages of activities: identification, product preparation, and evaluation. Overall, our program succesfully transferred the method of ”pokak” production to participants. Such product is projected ”local souvenirs” for tourists visiting Giligenting. In long term, the product can be one of attractive items for visitors. In addition, the future development was also arranged, including more intense product endorsement, packaging enhancement, and scientific studies to estimate shelf life and nutrition.